A Public Safety Compliance Model of Safety Behaviors in the Age of the COVID-19 Pandemic - Mohammad Al-Bsheish PhD; Mu'taman Jarrar PhD; Amanda Scarbrough PhD (SAGE Publishing, 2021)
The outbreak of COVID-19 has placed a heavy burden on society, threatening the future of the entire world as the pandemic has hit health systems and economic sectors hard. Where time moves fast, continuing curfews and lockdown is impossible. This paper assembles three main safety behaviors, social distancing, wearing a facemask, and hygiene in one model (PSC Triangle) to be practiced by the public. Integrating public safety compliance with these behaviors is the main recommendation to slow the spread of COVID-19. Although some concerns and challenges face these practices, the shifting of public behaviors to be more safety-centered is appropriate and available as an urgent desire exists to return to normal life on the one hand and the medical effort to find effective cure or vaccine that has not yet succeeded on the other hand. Recommendations to enhance public safety compliance are provided.